Penguatan Peran Masjid dalam Pemberdayaan Masyarakat melalui Program Sekolah Manajemen Masjid Indonesia - Abdul Wasik; Permatasari, Yovita Dyah; Hadliq Millati Waddin, Moch. Aufal (CV. Agrapana Media, 2026)
Mosques play a strategic role in community development, not only as centers of ritual worship but also as social, educational, and empowerment institutions. However, mosque governance in Indonesia still faces various challenges, including weak program planning, low financial transparency, limited digital literacy, and suboptimal involvement of congregations and young generations. In this context, the Indonesian Mosque Management School (Sekolah Manajemen Masjid Indonesia/SMMI) was initiated as a community service medium designed to strengthen the capacity of mosque administrators through an educative, participatory, and transformative approach based on the real needs of mosque communities. The main objective of SMMI is to enhance the managerial competence of mosque administrators so that they are able to implement professional, accountable, and community-oriented mosque governance. Specifically, this program aims to foster awareness among mosque managers regarding the importance of institutional strengthening, financial transparency, digital technology utilization, and the development of the social and economic roles of mosques. Through SMMI, mosques are directed to transform into centers of Islamic civilization that are inclusive, adaptive to contemporary challenges, and sustainable. The community service method applied in SMMI adopts a participatory-educative approach by positioning participants as active subjects throughout all stages of the program. This method is implemented through needs assessment, classical training, interactive discussions, practical simulations, field mentoring, evaluation, and the formulation of follow-up action plans. The approach is enriched by the principles of andragogy and experiential learning, enabling participants not only to acquire theoretical knowledge but also to develop practical skills that can be directly applied in managing their respective mosques. The results of the community service program indicate a significant improvement in the capacity of mosque administrators in terms of institutional management, organizational structuring, program planning, and transparent digital-based financial management. In addition, participants began initiating mosque-based community empowerment programs, such as strengthening the community economy, engaging youth participation, and utilizing social media for da‘wah and congregational services. Conceptually, this program also reinforces a mosque governance model based on the values of Intellectuality, Spirituality, and Integrity (ISI) as the foundation for transforming mosques into professional and empowered community institutions.